Photographic literacy : cameras in the hands of Russian authors - Reischl, Katherine M. H. (Cornell University Press, 2018)
"A primer in photographic literacy, focused on the sites of contact between photography and literary writing over roughly seventy years, this book traces the visual consciousness of modern Russian literature in the twentieth century as captured through the lens of the Russian author-photographer"--